2017
DOI: 10.1080/2162402x.2017.1412910
|View full text |Cite
|
Sign up to set email alerts
|

Repolarizing heterogeneous leukemia-associated macrophages with more M1 characteristics eliminates their pro-leukemic effects

Abstract: Macrophages exhibit phenotypic heterogeneity under both physiological and pathological conditions. Applications targeting M2-like tumor-associated macrophages (TAMs) improve outcome in solid tumors. Considerable differences are detected between leukemia-associated macrophages (LAMs) and TAMs. However, application to induce M1 characteristics in heterogeneous LAMs has not been established. Here we analyzed clinical relevance of macrophage phenotypes in human acute myeloid leukemia (AML), studied phenotypic evol… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
85
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 78 publications
(88 citation statements)
references
References 49 publications
3
85
0
Order By: Relevance
“…A two-dimensional illustration was established to describe the activation phenotype of macrophages (15). For each gene, the value of the Ly6C + F4/80 + macrophage subset from normal spleen or liver was designated as 0, respectively.…”
Section: Two-dimensional Illustration Of Macrophage Phenotypesmentioning
confidence: 99%
See 2 more Smart Citations
“…A two-dimensional illustration was established to describe the activation phenotype of macrophages (15). For each gene, the value of the Ly6C + F4/80 + macrophage subset from normal spleen or liver was designated as 0, respectively.…”
Section: Two-dimensional Illustration Of Macrophage Phenotypesmentioning
confidence: 99%
“…The LAM subsets showed considerable differences ( Figure 2F). To obtain an intuitive views of the phenotypic evolution of LAM subsets, a two-dimensional illustration of macrophage phenotypes was used (15). Interestingly, Ly6C + LAM was in M1 area at the early and middle stages of leukemia, whereas both splenic Ly6Cand F4/80 hi LAM was in M2 area during leukemia progression.…”
Section: Monocytes Differentiate Into Macrophage Subsets In Resting Lmentioning
confidence: 99%
See 1 more Smart Citation
“…Yang et al further confirmed that the number of CD163 + M2-like TAMs was correlated with worse prognosis in AML patients with splenic TAMs exhibiting more M2-characteristics than BM-TAMs. Additionally, they found that Interferon Regulatory Factor 7 (IRF7) contributed to the M1-polarization of TAMs through activation of the SAPK/JNK pathway and subsequent activation of the IRF7-SAPK/JNK pathway resulted in more M1-like TAMs, which was correlated with prolonged survival in leukemic mice [28].…”
Section: Acute Myeloid Leukemiamentioning
confidence: 99%
“…AML promotes the polarization of leukemia-supporting macrophages (47). Yang and colleagues further found that, in patients, leukemia associated macrophages are heterogeneous, with both M1- and M2-like leukemia associated macrophages (48). M2-like leukemia associated macrophages were associated with a poor prognosis.…”
Section: Features Of Immune Dysregulation In Amlmentioning
confidence: 99%